Oscillation of Second Order Impulsive Differential Equations with Nonpositive Neutral Coefficients (Journal of Nonlinear Modeling and Analysis, 2024)
In this work, sufficient conditions are established for a class of nonlinear second order neutral impulsive differential equations to have oscillatory solutions with nonpositive neutral coefficient. Our results extend and complement some of the known results in the literature. Examples are given to illustrate our results.